A meta-analysis of renal outcomes in living kidney donors. Issue 24 (June 2016) - Li, Sha-Sha; Huang, Yan-Mei; Wang, Min; Shen, Jian; Lin, Bing-Jie; Sui, Yi; Zhao, Hai-Lu
Abstract : Abstract: Given the increased burden of end-stage renal disease (ESRD), renal outcomes of kidney donation by living donors are of particular interest. PubMed, ProQuest, MEDLINE, EMBASE, Chinese national knowledge infrastructure, and Wanfang databases were searched for clinical outcomes of living kidney donors (LKDs) including renal death, ESRD, proteinuria/albuminuria, and renal function after donation. We included 62 studies from 19 countries involving 114, 783 kidney donors and nondonors to evaluate the renal consequences less than 6 months, 6 months to 5 years, 5 to 10 years, and 10 years onward after donation. The pooled data showed that uninephrectomy significantly decreased glomerular filtration rate and creatinine clearance rate in parallel with increased serum creatinine concentration (all P  < 0.05). The drastic changes in renal function occurred within 6 months rather than 5 to 10 years after donation. Ten years and onward, rate of proteinuria/albuminuria increased gradually: microalbuminuria from 5.3% to 20.9%, proteinuria from 4.7% to 18.9%, and overt proteinuria from 2.4% to 5.7% (all P  < 0.05). Prevalence of ESRD was 1.1%. All-cause mortality was 3.8% and all the renal deaths on average occurred 10 years postnephrectomy. LKDs might have aggravated glomerular filtration and creatinine clearance within 6 months after donation. Five years and onward, albuminuria, proteinuria, ESRD, and death might be the major concerns of LKDs. Long-term studies may clarify the survival time after donation. Abstract : Supplemental Digital Content is available in the text